Contribution of active hair-bundle motility to nonlinear amplification in the mammalian cochlea - Nin, Fumiaki; Reichenbach, Tobias; Fisher, Jonathan A. N.; Hudspeth, A. J. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
The cochlea's high sensitivity stems from the active process of outer hair cells, which possess two force-generating mechanisms: active hair-bundle motility elicited by Ca2+ influx and somatic motility mediated by the voltage-sensitive protein prestin. Although interference with prestin has demonstrated a role for somatic motility in the active process, it remains unclear whether hair-bundle motility contributes in vivo. We selectively perturbed the two mechanisms by infusing substances into the endolymph or perilymph of the chinchilla's cochlea and then used scanning laser interferometry to measure vibrations of the basilar membrane. Blocking somatic motility, damaging the tip links of hair bundles, or depolarizing hair cells eliminated amplification. While reducing amplification to a lesser degree, pharmacological perturbation of active hair-bundle motility diminished or eliminated the nonlinear compression underlying the broad dynamic range associated with normal hearing. The results suggest that active hair-bundle motility plays a significant role in the amplification and compressive nonlinearity of the cochlea.
CRIS-Team Scopus Importer:2021-02-25
Keywords: Auditory system; Hopf bifurcation